Clinical Outcomes of Weight-Based Norepinephrine Dosing in Underweight and Morbidly Obese Patients: A Propensity-Matched Analysis. (June 2020) - Kotecha, Aditya A.; Vallabhajosyula, Saraschandra; Apala, Dinesh R.; Frazee, Erin; Iyer, Vivek N.
Background: Weight-based dosing strategy for norepinephrine in septic shock patients with extremes of body mass index has been lesser studied. Methods: This historical study of adult septic shock patients was conducted from January 1, 2010, to December 31, 2015, at all intensive care units (ICUs) in Mayo Clinic, Rochester. Patients with documented body mass index were classified into underweight (body mass index <18.5 kg/m 2 ), normal weight (18.5-24.9 kg/m 2 ), and morbidly obese (≥40 kg/m 2 ) patients. Patients with repeat ICU admissions, ICU stay <1 day, and body mass index 25 to 39.9 kg/m 2 were excluded. The primary outcome was in-hospital mortality, and secondary outcomes included cumulative norepinephrine exposure acute kidney injury, cardiac arrhythmias, and 1-year mortality. Two-tailed P < .05 was considered statistically significant. Results: From 2010 to 2015, 2016 patients met inclusion—145, 1406, and 466 patients, respectively, in underweight, normal weight, and morbidly obese cohorts. Underweight patients used the highest peak dose and absolute exposure was greatest for morbidly obese patients. In-hospital mortality decreased with increasing log10 body mass index: 41.4% (underweight), 28.4% (normal weight), and 24.7% (morbidly obese), respectively ( P < .001); however, this relationship was not noted at 1 year. Unadjusted log10 norepinephrine cumulative exposure (mg) was associated with higher in-hospital mortality, acute kidney injury, cardiac arrhythmias, and 1-year mortality. After adjustment for demographics, body mass index, comorbidity, and illness severity, log10 norepinephrine exposure was an independent predictor of in-hospital mortality (odds ratio 2.4 [95% confidence interval, 2.0-2.8]; P < .001) and 1-year mortality (odds ratio 1.7 [95% confidence interval, 1.5-2.0]; P < .001). In a propensity-matched analysis of 1140 patients, log10 norepinephrine was an independent predictor of in-hospital mortality (odds ratio 2.2 [95% confidence interval, 1.8-2.6]; P < .001). Conclusions: Morbidly obese patients had lower in-hospital mortality but had higher 1-year mortality compared to normal weight and underweight patients. Cumulative norepinephrine exposure was highest in morbidly obese patients. Total norepinephrine exposure was an independent mortality predictor in septic shock.